Characterization of Nickel Thin Films as Strain Sensors for Wearable Health Monitoring System - Amrang, Nur Khairunnisa; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2026)
The rapid Evolution of wearable electronics has established a high demand for flexible, reliable sensors capable of continuous physiolohical monitoring. This research inbestigates the microstructural, optical, and electrical Evolution of nickel (Ni) thin flms deposited on flexible Polyethylene Terephthalate (PET) substrates to evaluate their suitability for wearable strain sensor applications. The study aims to identify the percolation threshold and analyze the relationship between film thickness and sensing performance. Nickel films were deposited via DC magnetron sputtering at varying intervals of 6, 12, 18, 24, 30, and 36 minutes. Characterization was performed using Scanning Electron Microscopy (SEM) for morphology, Atomic Force Microscopy (AFM) for surface topography, Spectroscopic Elllipsometry for thickness measurement, and a 4-point probe for electrical resistivitiy. Results confirmed a Volmer-Weber island.-growth mechanism, with the critical percolation threshold occuring at the 24-minute mark. This threshold coincided with a significant optical transmittance dip of approximately 51.3% caused by maximal diffuse light scattering from peak surface roughness. While structural analysis confirmed the formation of a continuous film by the 36 minute mark ( 27 nm), 4-point probe measurements revealed persistente electrical insulation across all samples. This insulating Behaviour is attributed to spontaneuous grain-boundary oxidation and the formation of Nickel Oxide (NiO) during the sputtering process. The study concludes that while structural percolation is achievable, the Chemical reactivity of nickel requires in-situ encapsulation or inert environments to maintain the electrical conductivitiy necesary for functional wearable sensors.